The Nasal Width and Boxiness Index: Introduction and Pilot Study on Reliability and Validity of Sonographic Morphometry - Tasman, Abel-Jan; Litschel, Ralph (Facial Plastic Surgery, 2018)
Both intended and unintended surgical modifications of nasal width and shape of the nasal tip continue to be of interest to the rhinoplasty surgeon. As validated instruments for quantifying width and boxiness are lacking, the objective of this study was to introduce a width index and a boxiness index for the nasal dorsum and the nasal tip. A width index and a boxiness index were defined within the methodological limits of noncontact sonography. The reliability of both indices was studied by comparing the measurements of two examiners on the noses of five volunteers. The validity of the indices was studied by correlating the sonographic width and boxiness with the 5-point Likert scale ratings of photographs of 5 noses by 21 lay persons. Nasal width was defined as the diameter at a distance of 5 mm from the skin surface on a sonographic cross-section perpendicular to the skin surface. Boxiness was defined as the quotient of width at a depth of 1 and 5 mm. Bland–Altmann analysis revealed negligible bias between both examiners and 95% of limits of agreement of 13, 7, and 13% for width at 1 mm, width at 5 mm, and boxiness, respectively. Corresponding Pearson's correlation coefficients were r = 0.93, r = 0.93, and r = 0.71. The correlation between the cumulative lay persons' scores and sonographic width and boxiness were r = 0.97, r = 0.66, and r = 0.81 for nasal tip width, dorsal width, and boxiness, respectively. Both the width at a depth of 5 mm as measured with sonography and the boxiness index that is defined as width at a depth of 1 mm divided by the width at a depth of 5 mm may prove to be acceptable surrogate parameters for width and boxiness of the nose in comparative morphometric studies.
Keywords: rhinoplasty; morphometry; sonography; nasal width